Women's Representation and Implications for Fairness, Trust, and Performance in Local Government: A Survey Experiment in Sri Lanka. (December 2022) - Baniamin, Hasan Muhammad; Jamil, Ishtiaq
How do quotas for women in Sri Lanka's local government institutions affect key governance indicators such as perceived fairness, institutional trust, and perceived performance? These dimensions of governance are underexplored in the context of gender quota policies in patriarchal societies like that of Sri Lanka. The study hypothetically varied the quota provision for women (decrease to 10%, increase to 45%, or keep at the current 25%) in local government, and then tried to understand people's opinions about the three governance indicators. When examining the results of the experiment (around 1, 200 samples), it was found that perceived fairness, institutional trust, and perceived performance increased along with the greater quota provision. Possible mechanisms for the increases in institutional trust and perceived performance may be associated with the signal of fairness generated by the increase of quota provision for women.